(untitled) (International Journal of Environmental Sciences, 2025)
Human Resources form an integral part of any business organization whether big, small or medium. It is the people who can make or break an organization. Theoretically, HRM is a management function that helps managers to plan, recruit, select, train, develop, compensate or remunerate, maintain and retain employees for an organization. Employee engagement refers to the emotional commitment, motivation, and dedication that employees have towards their jobs and the organization. “The Sustainable Development Goals (SDGs), established by the United Nations in 2015, consist of 17 global goals that aim to address various social, environmental, and economic challenges, having ultimate aim of achieving a sustainable future for all.” An engaged employee drives the organization forward and enables the organization to attain the globally applicable and universal SDGs. The current research paper highlights the increasing importance of understanding the relationship between Employee Engagement and attainment of Sustainable Development Goals (SDGs) which would lead to an improved global environment. The paper is a bibliometric analysis 207 articles published in Scopus Indexed Journals for the Keywords “Sustainable Development Goals” and “Human Resource Management”. It shows the relevance of the relationship between SDGs and HRM by outlining the emerging trends. Since engagement of employees forms the crucial part of HRM. Therefore, the paper also bibliometrically analyzes 34 articles (Scopus indexed journals) specifically for the keywords “Employee Engagement” and “Sustainable Development Goals”. This analysis brought out valuable insights about the significance and linkages between employee engagement and Sustainable Development Goals. The Bibliometric Analysis was conducted using VosViewer and the findings of the research paper reveal core themes, most relevant authors, countries of publication, most cited papers, most relevant sources, most relevant keywords associated with the three terms “Employee Engagement”, “Sustainable Development Goals” and Human Resource Management”.